An epidemiological study to evaluate the use of vitamin K antagonists and new oral anticoagulants among non-valvular atrial fibrillation patients in Turkey- AFTER-2 study design - Ertas, Faruk; Kaya, Hasan; Yildiz, Abdulkadir; Davutoglu, Vedat; Kiris, Abdulkadir; Dinc, Lale; Toprak, Nizamettin (Turkish Soc Cardiology, 2015)
Objectives: Atrial fibrillation (AF) is one of the most common causes of preventable ischemic stroke and is related to increased cardiovascular morbidity and mortality. There is a lack of data in Turkey on the use of new oral anticoagulants (NOACs), and time in therapeutic INR range (TTR) in vitamin K antagonist users and AF management modality. In this multi-center trial, we aimed to analyze, follow and evaluate the epidemiological data in non-valvular AF patients. Study design: Four thousand one hundred consecutive adult patients from 42 centers with at least one AF attack identified on electrocardiography will be included in the study. Patients with rheumatic mitral valve stenosis and prosthetic valve disease will be excluded from the study. At the end of one year, the patients will be evaluated in terms of major cardiac end points (death, transient ischemic attack, stroke, systemic thromboembolism, major bleeding and hospitalization). Results: First results are expected in June 2015. Data about major cardiovascular end-points will be available in January 2016. Conclusion: The rates and kind of oral anticoagulant use, TTR in vitamin K antagonist users and main management modality applied in non-valvular AF patients will be determined by AFTER-2 study. In addition, the rate of major adverse events (MACEs) and the independent predictors of these MACEs will be detected (AFTER-2 Study ClinicalTrials. gov number, NCT02354456.).
Keywords: Anticoagulant agent; atrial fibrillation/epidemiology; drug utilization; electrocardiography; international normalized ratio; warfarin